STRATEGI KOMUNIKASI RRI DALAM MEMPERTAHANKAN EKSISTENSI SEBAGAI MEDIA PENYIARAN KREATIFITAS ANAK MUDA DI ERA MILENIAL DI PRO 2 RRI PALANGKA RAYA - Rahman, Sirajul; Martalino, Januardo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This study aims to describe RRI's COMMUNICATION STRATEGY IN MAINTAINING EXISTENCE AS A CREATIVITY BROADCASTING MEDIA OF YOUTH IN THE MILENIAL ERA IN PRO 2 RRI PALANGKA RAYA. Young People at RRI Palangka Raya. The method used in this study is a qualitative descriptive method which describes a fact, symptom or phenomenon found in the field or which is studied and then explained based on the picture, the data collection method used is primary data and secondary data is carried out in natural settings (natural conditions). , primary data sources, and data collection techniques mostly on participatory observation and in-depth interviews. The data analysis method was carried out per subject by looking at the conditions in each session. The results showed that there was a pattern of communication indicators that caused a person's interest in listening to radio to decrease, namely Media and Effects that influenced the Existence of Pro2 RRI Palangkaraya, but behind that were the efforts of PRO2 RRI Palangkaraya in attracting listeners with promotional strategies through social media. The conclusion only works quite effectively because the Effects and Channels/Media aspects greatly affect a person's interest in listening to radio in the current Millennials era.